Sustainable development: Genesis, challenges and perspectives - GBEKLEY, Efui Holaly; GBEKLEY, Abla-Sika Hanou; ANNOUAR, Yassir; ALI, Abdourahamane Aissa Ghanny Vanessa; KOULA, Fodoh Clefasse (Edelweiss Applied Science and Technology, 2024)
The notion of sustainable development appeared in a period when humanity, prey to the conse-quences of the anarchic destruction of the environment, decided to change the paradigm of eco-nomic development called bad (bad) development to turn towards good development or ecode-velopment. If in the countries of the North, the concept is in phase with an adaptation or even an adequacy with the system of governance, this is not the case in the countries of the South. There is a need to rediscover this concept and do a fairly complete rereading of the proposed actions. The objective of this review is to present the facts, challenges and perspectives on sustainable development. Methodology: A systematic search was carried out in the Scopus and Google Scholar database using the key concepts: Sustainable Development, development indicators, ur-ban revitalization, eco-district, SOUTH countries. 69 selected articles relate to theoretical studies, field studies, study reports, international conferences and summits and expert declarations. Sus-tainable development takes into account the economic, social, cultural and especially environ-mental aspects which rhyme with a new governance policy where the actors are made up of rep-resentatives of grassroots communities: this is governance from below. The consequence is ur-ban governance which takes into account the priority issues of poor populations gathered in pe-ripheral districts which must be transformed into eco-districts. The approach to sustainable de-velopment is to evolve the principles and frameworks of city and regional planning by integrat-ing new economic, social and environmental issues. This gradually involves numerous modifi-cations by moving from a compartmentalized system of city governance to an integrated city management system or better to inclusive governance. Halfway to its completion, in view of the urban challenges, especially environmental ones, there is an urgent need for a reassessment of the strategies deployed to achieve the objectives of sustainable development globally and specif-ically in the global south.